Potential Serum Biomarkers in Prenatal Diagnosis of Placenta Accreta Spectrum - Zhang, Tianyue; Wang, Shaowei (Frontiers in Medicine, 2022)
Placenta accreta spectrum (PAS) refers to the abnormal invasion of trophoblastic tissues.Because of its increasing morbidity and possibility of catastrophic outcomes, PAS requires an antenatal diagnosis and making full preparations in advance to realize safe delivery. Current clinical screening modalities for PAS are not always conclusive.Recently, it has been reported that bio-markers detected in maternal serum have the potential for predicting PAS during pregnancy. Some of these biomarkers,such as β-hcg,AFP,PAPP-A and cffDNA,can be clinically detected.It is convinece for us to test and compare with standard threshold.However,how can we distinguishing PAS from other pregnancy complications through these biomarkers remains complicated.Some biomarkers are specific, such as microRNA and plancenta-specific mRNA.They are stability and reliability.These biomarkers are currently research hotspots.This study aims to summarize the characteristics of the newly reported biomarkers and to point out their potential application and current limitations to provide a basis for future research.Finally, the combination of imageological examination and biomarkers will be an attractive future theme to study in diagnosing this challenging condition.